Blockchain-based key management scheme for distributed networks - Qianyi DAI; Kaiyong XU; Song GUO; Guoming CAI; Zhicheng ZHOU (网络与信息安全学报)
Regarding the difficult key management and excessive communication overhead in the distributed group networks,KMSBoB-Key management schemes based on blockchain was proposed,featuring key management and transmitting procedure based on blockchain in distributed group networks.Meanwhile,the all-member mining process of blockchain and the MTI/CO protocol process were combined to establish a protocol of dynamically generated session key,so as to streamline key management strategies in cross-heterogeneous autonomous domains.According to simulation testing and result analysis,KMSBoB is safe and effective,with less communication overhead and higher expansibility than traditional key management schemes.